Voluntary' and 'Involuntary' early retirement: an international analysis - David Dorn; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2007)
Recent literature makes a distinction between 'voluntary' and 'involuntary' early retirement, where 'involuntary' early retirement results from employment constraints rather than from a preference for leisure relative to work. This paper analyzes 'voluntary' and 'involuntary' early retirement based on international microdata covering 19 industrialized countries. The results show that 'involuntary' early retirement is particularly widespread in Continental Europe. Countries facing economic recessions and having strict employment protection legislation have higher shares of 'involuntary' retirements among early retirees. Generous early retirement provisions of the social security system do not only make 'voluntary' early retirement more attractive for individuals, but also induce firms to push more employees into early retirement.
urn:nbn:de:101:1-2008041034
Keywords: 330; Flexible Altersgrenze; Unfreiwillige Arbeitslosigkeit; Gesetzliche Rentenversicherung; Kündigungsschutz; Industriestaaten; Westeuropa